Strategi Penenun Ulos dalam Mempertahankan Nilai-Nilai Budaya pada Masyarakat Batak Toba di Desa Siraja Hutagalung Kecamatan Siatas Barita - Joan Lumbantobing; Wensdy Sitindaon; Martua Sihaloho; Feriel Amelia Sembiring; David Fero (Jurnal Publikasi Manajemen Informatika, 2025)
This thesis is motivated by the existence of the Strategy of Ulos weavers in maintaining the cultural values ​​of Ulos in the Batak Toba Community in Siraja Hutagalung Village, Siatas Barita District. With the Strategy of Ulos weavers, the Community understands more and maintains the sustainability of the values ​​​​in Ulos. With this strategy, the Community will be more enthusiastic in weaving, in addition to meeting their needs, Ulos is also a culture that cannot be removed. This study uses a qualitative method with a descriptive approach whose data collection is through observation, interviews, and documentation of several informants, namely the village head, cultural figures, and the Ulos weaver community of Siraja Hutagalung Village. Through this study, a description of the Strategy of Ulos weavers who still maintain the cultural values ​​​​of Ulos in Siraja Hutagalung Village was obtained. The government and community participate in maintaining the cultural values ​​​​of Ulos so that they can develop and be known by many people.